Quantification of proteins in sample buffer for sodium dodecyl sulfate-polyacrylamide gel electrophoresis using colloidal silver - Dráber, P (Electrophoresis, 1991)
A rapid and simple assay for quantification of proteins in sodium dodecyl sulfate-sample buffer is described. Proteins are bound to a nitrocellulose membrane, stained with colloidal silver, and quantified by transmission densitometry. The staining requires 1 microL of protein sample and takes less than 20 min. Good linearity between the staining intensity and amount of proteins is in the range of 5-100 ng.
Keywords: Silver Nitrate; Collodion; proteiny; pufry; Colloids; dodecylsíran sodný; denzitometrie; koloidy; Buffers; dusičnan stříbrný; Densitometry; Sodium Dodecyl Sulfate; elektroforéza v polyakrylamidovém gelu; membrány umělé; Electrophoresis, Polyacrylamide Gel; barvení a značení; kolodium; Membranes, Artificial; Staining and Labeling; Proteins